Your host, Walt Disney TV memories, 1956-1965 - Disney, Walt 1901-1966; Buena Vista Home Entertainment (Firm) (Burbank, Calif Distributed by Buena Vista Home Entertainment, 2006)
Celebrate Walt Disney with this look back at several of the most memorable hours from his groundbreaking television shows
Disc 1: 1956 Where do stories come from? -- $g 1957 Fourth anniversary show -- 1959 $t Kodak presents Disneyland '59 -- $t Galleries -- My Dad, Walt Disney. $g Disc 2: 1961 Backstage party -- 1965: $t Disneyland tenth anniversary show -- I captured the king of the Leprechauns -- Disneyland USA at Radio City Music Hall -- Working with Walt
Title from container
1
Keywords: Television programs -- United States; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs